PENERAPAN KOMUNIKASI PEMIMPIN TRANSFORMASIONAL DALAM MENINGKATKAN MOTIVASI KARYAWAN (Studi Kasus Komunikasi Organisasi di Divisi Corporate Secretary Kantor Pusat PT Jasa Marga (Persero) Tbk.) - Sri Ardalita (Universitas Mercu Buana, 2017)
Essentially a leader has a regular language, good words integrated into the behavior and actions of delivery, direction and control. In the organization known as the art of leadership, meaning that every idea produced is clear and weighted, the application of transformational leadership communication in persuasive techniques. In The Five Canon of Rhetoric known as invention, arrangement, style, delivery, memory, this is in the direction of transformational leadership to the Vice President in the Corporate Secretary Division characterized by Charisma, Inspiration, Intellectual Stimulation, Individual Considerations. This leadership style can influence followers to do more than expected to maintain employee motivation. The collected data was obtained from interviews of 7 informants and documentation studies, with the Instrumental Study Case Study method, and using post-positivism paradigm and using the theory triangulation technique. The results, with the Five Canon of Rhetoric are very useful when applied to an organization as an encouragement of employees to make employees motivated because not only convey persuasive information but also for others are also willing to accept and take positive actions. So that, will be created a harmonious atmosphere between the subordinates as well avoid miss communication.Keywords: Transformational Leadership Communication, Canons of Rhetoric, Employee Motivation